Poly(N,N-dimethylacrylamide)-coated upconverting NaYF4:Yb,Er@NaYF4:Nd core–shell nanoparticles for fluorescent labeling of carcinoma cells - Viktoriia Oleksa (Nature Portfolio, 2021)
Abstract Upconverting luminescent lanthanide-doped nanoparticles (UCNP) belong to promising new materials that absorb infrared light able to penetrate in the deep tissue level, while emitting photons in the visible or ultraviolet region, which makes them favorable for bioimaging and cell labeling. Here, we have prepared upconverting NaYF4:Yb,Er@NaYF4:Nd core–shell nanoparticles, which were coated with copolymers of N,N-dimethylacrylamide (DMA) and 2-(acryloylamino)-2-methylpropane-1-sulfonic acid (AMPS) or tert-butyl [2-(acryloylamino)ethyl]carbamate (AEC-Boc) with negative or positive charges, respectively. The copolymers were synthesized by a reversible addition-fragmentation chain transfer (RAFT) polymerization, reaching M n ~ 11 kDa and containing ~ 5 mol% of reactive groups. All copolymers contained bisphosphonate end-groups to be firmly anchored on the surface of NaYF4:Yb,Er@NaYF4:Nd core–shell nanoparticles. To compare properties of polymer coatings, poly(ethylene glycol)-coated and neat UCNP were used as a control. UCNP with various charges were then studied as labels of carcinoma cells, including human hepatocellular carcinoma HepG2, human cervical cancer HeLa, and rat insulinoma INS-1E cells. All the particles proved to be biocompatible (nontoxic); depending on their ξ-potential, the ability to penetrate the cells differed. This ability together with the upconversion luminescence are basic prerequisites for application of particles in photodynamic therapy (PDT) of various tumors, where emission of nanoparticles in visible light range at ~ 650 nm excites photosensitizer.